KONSTRUKSI POLA DASAR KONSELING BERBASIS BUDAYA DAN NILAI RELIGIUS PESANTREN - Sukatin; M Rifqi Dzannuroini; Wanda Rizki Romadhan; Aldi Khoiron; Aldi Azhari (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Multicultural counseling based on pesantren values and Islamic spirituality serves as an innovative approach to preventing bullying in pesantren environments. This study analyzes how the integration of pesantren values such as discipline, solidarity, and Islamic spirituality can shape tolerant and empathetic student characters, thereby reducing the risk of bullying. Through qualitative methods involving in-depth interviews with pesantren caregivers and students, the results indicate that this counseling is effective in enhancing cultural and spiritual awareness, which acts as a preventive measure against interpersonal conflicts. Practical implications include the development of routine counseling programs in pesantren to support harmonious and inclusive learning environments.